Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Towards efficient conversion of sucrose to 1,2-propanediol selectively over Cu-La on activated carbon support - Anilan, Anusree Elavanaparambil; Sreekantan, Sreejith; Racha, Arundhathi; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2025)
In this study, we investigated the conversion of sucrose to 1,2-propanediol (1,2-PDO) using various Cu-La metals supported on activated carbon (AC), a versatile support known for its hydrophobicity and high surface area. Among the catalysts tested, 6% Cu-20% La/AC demonstrated the highest activity, achieving a 72% yield of 1,2-PDO under optimal reaction conditions of 200 degrees C, 40 bar H2, and 6-h reaction time. Comparative studies using cellulose, sucrose, glucose, and fructose as substrates identified sucrose as the most favorable feedstock for 1,2-PDO production. Detailed catalyst characterization (XRD, TEM, FE-SEM, TPR, TPD, XPS) revealed that the high dispersion, presence of metallic copper, and synergy between Cu and La, along with the presence of optimal acidic and basic sites, were responsible for the catalyst's high selectivity of 1,2-PDO. Additionally, the effect of different supports, including HY, NaY, HZSM-5, NaZSM-5, gamma-Al2O3, and AC, on sucrose conversion was examined, with AC showing superior performance. The catalyst's reusability was also assessed.Graphical abstractInvestigation of Cu-La metals supported on activated carbon for the catalytic conversion of sucrose to 1,2-propanediol, with an emphasis on choice of support, feedstock selection, catalyst performance, and stability under optimized reaction conditions.
Keywords: 1; 2-Propanediol; Biomass conversion; Biomass-to-chemicals; Hydrogenation